Sound-insulation flame-retardant fabric and preparation method thereof

Through the composite weaving technology of loaded microball kapok fiber and cashmere fiber, and the use of acrylic resin to finish the crosslinking agent, the problem of fabrics being difficult to achieve flame retardant and sound insulation at the same time in the prior art is solved, and the dual-effect flame retardant and strong sound insulation effects of the fabric are achieved.

CN119877280APending Publication Date: 2025-04-25南通和顺兴纺织集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901333.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

It is difficult for existing textile technology to achieve both flame retardant and sound insulation performance in fabrics, especially the high combustion of natural fibers and the sound insulation effect will become worse after treatment.

Method used

The inner layer is woven with loaded microspheres, and the cashmere fiber is woven with the outer layer covering both front and back sides of the inner layer. It is treated with acrylic resin to finish crosslinking agent to cause crosslinking between the fibers to form a hollow structure to improve flame retardant performance and sound insulation effect.

Benefits of technology

The fabric is achieved with dual-effect flame retardant effect and strong sound insulation performance, while improving the textileability and touch of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203254540000081
    Figure BDA0005203254540000081
Patent Text Reader

Abstract

The invention discloses a sound-insulation flame-retardant fabric and a preparation method thereof, and relates to the technical field of multi-layer fabrics. According to the method, firstly, through plasma treatment, grooves are formed in the surfaces of the kapok fibers, proper attachment points of hollow magnesium hydroxide microspheres with positive charges and polysiloxane microspheres with active hydroxyl are attached, a large number of gaps are reserved between the microspheres, and the microspheres and the hollow structures of the microspheres can achieve the powerful sound insulation effect through the synergistic effect. Secondly, weaving cashmere fibers into an outer layer to cover the front and back surfaces of the inner layer, finishing and cross-linking by using acrylic resin, and coating and cross-linking the two fibers; when the resin entering the hollow structure of the cashmere fiber is cooled and cured, a molecular chain curls up and the volume is reduced, and the hollow structure of the fiber is still retained, so that more and larger cavity structure carbon residues are formed when the fiber is combusted, and the double-effect flame-retardant effect is achieved through the synergistic effect of the carbon residues and the hollow magnesium hydroxide particles. The fabric prepared by the method has the effects of flame retardance and sound insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, in particular to a sound-insulating and flame-retardant fabric and a preparation method thereof. Background Art

[0002] Textile materials can be classified as porous sound-absorbing materials because they are loose, soft and porous. According to the sound absorption mechanism of porous sound-absorbing materials, when sound waves are incident on the surface of textile materials, the vibrations generated by the sound waves cause the movement of air in the gaps inside the textile materials and in the fiber pores. Air itself has the function of attenuating high-frequency sound waves. At the same time, the movement of air causes friction between yarns, between fibers and on the pore walls inside the fibers. Due to the effects of friction and viscosity, part of the sound energy is converted into heat energy. The air in the gaps and pores in the textile materials exchanges heat with the surrounding environment, making the textile materials have sound absorption properties.

[0003] In the existing textile technology, sound insulation materials are mostly made of natural fibers or sound insulation cavity structures. However, the flammability of natural fibers is very high and cannot meet the flame retardant requirements for fabrics. How to make the fabric have flame retardant effect while taking into account the sound insulation performance is the research direction of the present invention. Since natural cashmere fiber is a fiber with a hollow structure at the micron level, when the fabric is treated with finishing liquid, the finishing liquid can enter the fiber, which will cause the hollow structure of the cashmere fiber to be filled and the sound insulation effect to deteriorate. The microspheres attached to the surface of kapok fiber cause the effective factors of the fabric to fall off and fail due to external factors during daily use. How to more firmly bind the microspheres to the fiber surface is also one of the difficult problems. In response to the above problems, the present invention provides a sound insulation and flame retardant fabric and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a sound insulation and flame retardant fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a sound insulation and flame retardant fabric, wherein the sound insulation and flame retardant fabric is a composite fabric made of kapok fibers loaded with microspheres woven into an inner layer and cashmere fibers woven into an outer layer covering the front and back sides of the inner layer;

[0006] The sound insulation and flame retardant fabric is prepared by the following method:

[0007] (1) preparing a 0.1-2 mol / L magnesium sulfate aqueous solution, a 0.2-4 mol / L sodium hydroxide aqueous solution, and a 0.05 mol / L polyethylene glycol ether aqueous solution, mixing the magnesium sulfate aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 1:0.01-0.05 to form a mixed solution 1, and mixing the sodium hydroxide aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 2:0.01-0.05 to form a mixed solution 2, respectively passing through a pneumatic atomizing nozzle under the drive of compressed air to form an atomizing flow 1 and an atomizing flow 2, controlling the flow ratio of the liquid phase medium to the compressed air to be 1:7, collecting the magnesium hydroxide primary product after the spray impact precipitation is completed, and then stirring and aging for 1-3 hours, and then filtering the sample to obtain a filter cake, and drying it at 40° C. for 3 hours to obtain hollow magnesium hydroxide microspheres;

[0008] (2) Take 60 parts of deionized water, add 6-12 parts of methanol, heat to 50°C, add 9-15 parts of phenyltrimethoxysilane and 1-7 parts of methyltrimethoxysilane under stirring at 60 rpm, react for 30 minutes, add 0.6 parts of NaOH aqueous solution, react for 2 hours under stirring at 60 rpm, filter the filtrate, wash it with deionized water for 3 times, and dry it in an oven at 100°C for 2 hours to obtain copolymerized silsesquioxane microspheres; weigh 5 parts of kapok fiber, put it into the bath at 100°C and boil it for 120 minutes, and then put the kapok fiber into the bath. The fiber was taken out, washed with deionized water for 3 times, dried at 25°C for 2 hours, and then placed in a flat electrode excitation processor for plasma treatment to obtain pretreated kapok fiber; 1.2-1.6 parts of copolymerized silsesquioxane microspheres and 0.6-1 parts of hollow magnesium hydroxide microspheres were added to 40 parts of organic solvent and stirred at 60 rpm for 20 minutes to obtain a mixed solution, 5 parts of pretreated kapok fiber were immersed in the mixed solution, slowly stirred at 20 rpm for 30 minutes, and then taken out, washed with deionized water for 3 times, and then dried at 25°C for 3 hours to obtain finished kapok fiber;

[0009] (3) Three strands of finished kapok fiber are twisted into one strand and woven into an inner layer fabric; an outer layer is woven with cashmere fiber as raw material and covered on both sides of the inner layer, the outer layer is composed of a first warp yarn, a first weft yarn, a second warp yarn and a second weft yarn, the first warp yarn, the first weft yarn, the second warp yarn and the second weft yarn are woven alternately, and the first warp yarn and the first weft yarn are perpendicular to each other, and the second warp yarn and the second weft yarn are perpendicular to each other; the outer layer weaving is interlaced into the inner layer weaving to form a gram weight of 450g / m 2 Composite fabric: Put the composite fabric into the prepared acrylic resin finishing solution, the bath ratio is 1:10, the temperature is 120℃, soak for 45-75min, take it out, put it into an electric constant temperature blast drying oven at 60℃ and dry it for 1h to obtain the sound insulation and flame retardant fabric.

[0010] Furthermore, the stirring speed during aging in step (1) is 600-1000 rpm.

[0011] Furthermore, the concentration of NaOH in step (2) is 2 mol / L.

[0012] Furthermore, in step (2), the average particle size of the polysiloxane microspheres is 10-50 μm.

[0013] Furthermore, the concentration of the bath solution in step (2) is 20 g / L sodium hydroxide, 2 g / L anhydrous sodium sulfate, and the rest is deionized water.

[0014] Furthermore, in the step (2), the bath ratio of the kapok fibers when boiled in the bath liquid is 1:40.

[0015] Furthermore, the plasma power in step (2) is 1.0-4.0 kW.

[0016] Furthermore, the plasma treatment time in step (2) is 15-45s.

[0017] Furthermore, in the step (2), the organic solvent is tetrahydrofuran.

[0018] Furthermore, the finishing liquid in step (3) is an aqueous solution of acrylic resin with a concentration of 5-25 g / L.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The present invention uses kapok fibers loaded with microspheres to weave an inner layer, and uses cashmere fibers to weave an outer layer to cover the front and back sides of the inner layer, thereby protecting and improving the touch of the fabric. Acrylic resin is used as a finishing cross-linking agent to treat the entire fabric. The acrylic resin finishing will form a thin film on the surface of the fabric fiber, which covers the two fibers and causes cross-linking between the inner and outer fibers. The cashmere fiber also has a hollow structure. After the thermoplastic acrylic resin is used to coat the cashmere fiber, the molecular chain curls up during cooling and solidification. After film formation, the acrylic resin has high thermal expansion, and the resin volume inside the cashmere fiber is reduced. While the textile properties of the cashmere fiber are improved, the hollow structure of the fiber is still retained, so that the fiber forms more and larger cavity structure residual carbon when burning, which synergizes with the hollow magnesium hydroxide particles attached to the inner kapok fiber to achieve a double-effect flame retardant effect.

[0021] The inner layer is woven from kapok fibers; through plasma treatment, numerous circular grooves are generated on the surface of the kapok fibers due to the collision of ion beams, which provide suitable attachment points for the positively charged hollow magnesium hydroxide microspheres and the polysiloxane microspheres with active hydroxyl groups. Since the polysiloxane microspheres can chemically bond with the kapok fibers and are fixed in the grooves, and the polysiloxane microspheres and the kapok fibers have negatively charged hydroxyl groups, the hollow magnesium hydroxide microspheres can be firmly adsorbed into the grooves on the surface of the kapok fibers through electrostatic bonding. At the same time, a large number of gaps are left between the polysiloxane microspheres and the magnesium hydroxide microspheres, which can synergize with the hollow structure of magnesium hydroxide and kapok fibers to achieve a strong sound insulation effect. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of a sound insulation and flame retardant fabric prepared in the following examples as follows:

[0024] Flame retardancy: The same size of the embodiment and the comparative example were tested according to GB / T5455 textile combustion performance test.

[0025] Sound insulation: Take the same size of the embodiment and the comparative example to separate the noise source from the sound detector, and make the twelve-sided sound source emit a noise with an audio frequency of 100 Hz. Use the HS5671A noise spectrum analyzer to test the volume in the sealed cubic space (1 cm close to the inner surface of the fabric sample) and the volume outside the sealed cubic space (1 cm close to the outer surface of the fabric sample) to test the noise reduction rate. Noise reduction rate T% = [(noise source decibel) - (partition wall decibel)] / noise source decibel × 100%

[0026] Embodiment 1; (1) prepare 0.1mol / L magnesium sulfate aqueous solution, 0.2mol / L sodium hydroxide aqueous solution, 0.05mol / L polyethylene glycol ether aqueous solution, the magnesium sulfate aqueous solution and the polyethylene glycol ether aqueous solution are mixed in a molar ratio of 1:0.01 to form a mixed solution 1, the sodium hydroxide aqueous solution and the polyethylene glycol ether aqueous solution are mixed in a molar ratio of 2:0.01 to form a mixed solution 2, respectively, driven by compressed air through a pneumatic atomizing nozzle to form atomization flow 1 and atomization flow 2, the flow ratio of the liquid medium to the compressed air is controlled to be 1:7, after the spray impact precipitation is completed, the magnesium hydroxide primary product is collected, and then the speed is 600rpm to stir and age for 1h, and then the sample is filtered to obtain a filter cake, which is dried at 40°C for 3h to obtain hollow magnesium hydroxide microspheres;

[0027] (2) Take 60 parts of deionized water, add 6 parts of methanol, heat to 50°C, add 9 parts of phenyltrimethoxysilane and 1 part of methyltrimethoxysilane under stirring at 60 rpm, react for 30 minutes, add 0.6 parts of 2 mol / L NaOH aqueous solution, react for 2 hours under stirring at 60 rpm, filter the filtrate, wash it with deionized water for 3 times, and dry it in an oven at 100°C for 2 hours to obtain copolymerized silsesquioxane microspheres with an average particle size of 10 μm; prepare a bath solution with a concentration of 20 g / L sodium hydroxide, 2 g / L anhydrous sodium sulfate, and the rest of deionized water, weigh 5 parts of kapok fiber, and add it in a bath ratio of 1:40, 1:10 The kapok fibers were boiled in a bath at 0°C for 120 minutes, the kapok fibers were taken out, washed with deionized water for 3 times, dried at 25°C for 2 hours, and then placed in a flat electrode excitation processor for plasma treatment, with a power of 1.0 kW and a treatment time of 15 seconds to obtain pretreated kapok fibers; 1.2 parts of copolymerized silsesquioxane microspheres and 0.6 parts of hollow magnesium hydroxide microspheres were added to 40 parts of tetrahydrofuran and stirred at 60 rpm for 20 minutes to obtain a mixed solution, 5 parts of the pretreated kapok fibers were immersed in the mixed solution, slowly stirred at 20 rpm for 30 minutes, and then taken out, washed with deionized water for 3 times, and then dried at 25°C for 3 hours to obtain finished kapok fibers;

[0028] (3) Three strands of finished kapok fiber are twisted into one strand and woven into an inner layer fabric; an outer layer is woven with cashmere fiber as raw material and covered on both sides of the inner layer, the outer layer is composed of a first warp yarn, a first weft yarn, a second warp yarn and a second weft yarn, the first warp yarn, the first weft yarn, the second warp yarn and the second weft yarn are woven alternately, and the first warp yarn and the first weft yarn are perpendicular to each other, and the second warp yarn and the second weft yarn are perpendicular to each other; the outer layer weaving is interlaced into the inner layer weaving to form a gram weight of 450g / m 2 Composite fabric: The composite fabric is placed in a prepared 5g / L acrylic resin aqueous solution with a bath ratio of 1:10 and a temperature of 120°C. After soaking for 45 minutes, it is taken out and placed in an electric constant temperature blast drying oven at 60°C for drying for 1 hour to obtain a sound insulation and flame retardant fabric.

[0029] Example 2; (1) Prepare 1 mol / L magnesium sulfate aqueous solution, 2.1 mol / L sodium hydroxide aqueous solution, and 0.05 mol / L polyethylene glycol ether aqueous solution, mix the magnesium sulfate aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 1:0.03 to form a mixed solution 1, mix the sodium hydroxide aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 2:0.03 to form a mixed solution 2, and pass through a pneumatic atomizing nozzle under the drive of compressed air to form an atomization flow 1 and an atomization flow 2, respectively, and control the flow ratio of the liquid phase medium to the compressed air to be 1:7. After the spray impact precipitation is completed, the magnesium hydroxide primary product is collected, and then the reaction is stirred at a speed of 800 rpm for aging for 2 hours, and then the sample is filtered to obtain a filter cake, which is dried at 40°C for 3 hours to obtain hollow magnesium hydroxide microspheres;

[0030] (2) Take 60 parts of deionized water, add 9 parts of methanol, heat to 50°C, add 12 parts of phenyltrimethoxysilane and 4 parts of methyltrimethoxysilane under stirring at 60 rpm, react for 30 minutes, add 0.6 parts of 2 mol / L NaOH aqueous solution, react for 2 hours under stirring at 60 rpm, filter the filtrate, wash it with deionized water for 3 times, and dry it in an oven at 100°C for 2 hours to obtain copolymerized silsesquioxane microspheres with an average particle size of 30 μm; prepare a bath solution with a concentration of 20 g / L sodium hydroxide, 2 g / L anhydrous sodium sulfate, and the rest of deionized water, weigh 5 parts of kapok fiber, and add it in a bath ratio of 1:40, 1:10 The kapok fibers were boiled in a bath at 0°C for 120 minutes, and the kapok fibers were taken out, washed with deionized water for 3 times, dried at 25°C for 2 hours, and then placed in a flat electrode excitation processor for plasma treatment at a power of 2.5 kW and a treatment time of 30 seconds to obtain pretreated kapok fibers; 1.4 parts of copolymerized silsesquioxane microspheres and 0.8 parts of hollow magnesium hydroxide microspheres were added to 40 parts of tetrahydrofuran and stirred at 60 rpm for 20 minutes to obtain a mixed solution, 5 parts of the pretreated kapok fibers were immersed in the mixed solution, slowly stirred at 20 rpm for 30 minutes, and then taken out, washed with deionized water for 3 times, and then dried at 25°C for 3 hours to obtain finished kapok fibers;

[0031] (3) Three strands of finished kapok fiber are twisted into one strand and woven into an inner layer fabric; an outer layer is woven with cashmere fiber as raw material and covered on both sides of the inner layer, the outer layer is composed of a first warp yarn, a first weft yarn, a second warp yarn and a second weft yarn, the first warp yarn, the first weft yarn, the second warp yarn and the second weft yarn are woven alternately, and the first warp yarn and the first weft yarn are perpendicular to each other, and the second warp yarn and the second weft yarn are perpendicular to each other; the outer layer weaving is interlaced into the inner layer weaving to form a gram weight of 450g / m 2 Composite fabric: The composite fabric is placed in a prepared 15g / L acrylic resin aqueous solution with a bath ratio of 1:10 and a temperature of 120°C. After soaking for 60 minutes, it is taken out and placed in an electric constant temperature blast drying oven at 60°C for drying for 1 hour to obtain a sound insulation and flame retardant fabric.

[0032] Example 3; (1) Prepare 2 mol / L magnesium sulfate aqueous solution, 4 mol / L sodium hydroxide aqueous solution, and 0.05 mol / L polyethylene glycol ether aqueous solution, mix the magnesium sulfate aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 1:0.05 to form a mixed solution 1, mix the sodium hydroxide aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 2:0.05 to form a mixed solution 2, and pass through a pneumatic atomizing nozzle under the drive of compressed air to form an atomization flow 1 and an atomization flow 2, respectively, and control the flow ratio of the liquid medium to the compressed air to be 1:7. After the spray impact precipitation is completed, collect the magnesium hydroxide primary product, and then stir and age the reaction at a speed of 1000 rpm for 3 hours, then filter the sample to obtain a filter cake, and dry it at 40°C for 3 hours to obtain hollow magnesium hydroxide microspheres;

[0033] (2) Take 60 parts of deionized water, add 12 parts of methanol, heat to 50°C, add 15 parts of phenyltrimethoxysilane and 7 parts of methyltrimethoxysilane under stirring at 60 rpm, react for 30 minutes, add 0.6 parts of 2 mol / L NaOH aqueous solution, react for 2 hours under stirring at 60 rpm, filter the filtrate, wash it with deionized water for 3 times, and dry it in an oven at 100°C for 2 hours to obtain copolymerized silsesquioxane microspheres with an average particle size of 50 μm; prepare a bath solution with a concentration of 20 g / L sodium hydroxide, 2 g / L anhydrous sodium sulfate, and the rest of deionized water, weigh 5 parts of kapok fiber, and add it in a bath ratio of 1:40, The kapok fibers were boiled in a bath at 100°C for 120 minutes, and the kapok fibers were taken out, washed with deionized water for 3 times, dried at 25°C for 2 hours, and then placed in a flat electrode excitation processor for plasma treatment at a power of 4.0 kW and a treatment time of 45 seconds to obtain pretreated kapok fibers; 1.6 parts of copolymerized silsesquioxane microspheres and 1 part of hollow magnesium hydroxide microspheres were added to 40 parts of tetrahydrofuran and stirred at 60 rpm for 20 minutes to obtain a mixed solution, 5 parts of the pretreated kapok fibers were immersed in the mixed solution, slowly stirred at 20 rpm for 30 minutes, and then taken out, washed with deionized water for 3 times, and then dried at 25°C for 3 hours to obtain finished kapok fibers;

[0034] (3) Three strands of finished kapok fiber are twisted into one strand and woven into an inner layer fabric; an outer layer is woven with cashmere fiber as raw material and covered on both sides of the inner layer, the outer layer is composed of a first warp yarn, a first weft yarn, a second warp yarn and a second weft yarn, the first warp yarn, the first weft yarn, the second warp yarn and the second weft yarn are woven alternately, and the first warp yarn and the first weft yarn are perpendicular to each other, and the second warp yarn and the second weft yarn are perpendicular to each other; the outer layer weaving is interlaced into the inner layer weaving to form a gram weight of 450g / m 2Composite fabric: The composite fabric is placed in a prepared 25g / L acrylic resin aqueous solution with a bath ratio of 1:10 and a temperature of 120°C. After soaking for 75 minutes, it is taken out and placed in an electric constant temperature blast drying oven at 60°C for drying for 1 hour to obtain a sound insulation and flame retardant fabric.

[0035] Comparative Example 1; The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: take 60 parts of deionized water, add 9 parts of methanol, heat to 50°C, add 12 parts of phenyltrimethoxysilane and 4 parts of methyltrimethoxysilane under stirring at 60rpm, react for 30min, add 0.6 parts of 2mol / L NaOH aqueous solution, react for 2h under stirring at 60rpm, filter the filtrate, wash it with deionized water three times, and dry it in an oven at 100°C for 2h to obtain copolymerized silsesquioxane microspheres with an average particle size of 30μm; prepare a bath solution with a concentration of 20g / L sodium hydroxide, 2g / L anhydrous sodium sulfate, and the rest of deionized water, weigh 5 parts of kapok fibers were placed in a bath liquid at a bath ratio of 1:40 and 100°C and boiled for 120 minutes. The kapok fibers were taken out, washed with deionized water for 3 times, dried at 25°C for 2 hours, and then placed in a flat electrode excitation processor for plasma treatment at a power of 2.5 kW and a treatment time of 30 seconds to obtain pretreated kapok fibers. 1.4 parts of copolymerized silsesquioxane microspheres were added to 40 parts of tetrahydrofuran and stirred at 60 rpm for 20 minutes to obtain a mixed solution. 5 parts of the pretreated kapok fibers were immersed in the mixed solution, slowly stirred at 20 rpm for 30 minutes, and then taken out, washed with deionized water for 3 times, and then dried at 25°C for 3 hours to obtain finished kapok fibers. The remaining steps were the same as those in Example 2.

[0036] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different, and step (2) is changed to: prepare a bath solution with a concentration of 20 g / L of sodium hydroxide, 2 g / L of anhydrous sodium sulfate, and the rest being deionized water, weigh 5 parts of kapok fiber, put it into the bath solution at a bath ratio of 1:40 and boil it for 120 min at 100°C, take out the kapok fiber, wash it 3 times with deionized water, dry it at 25°C for 2h, and then put it into a flat electrode excitation processor for plasma treatment at a power of 2.5 kW and a treatment time of 30s to obtain pretreated kapok fiber; add 0.8 parts of hollow magnesium hydroxide microspheres to 40 parts of tetrahydrofuran and stir it at a speed of 60 rpm for 20 min to obtain a mixed solution, soak 5 parts of the pretreated kapok fiber in the mixed solution, slowly stir it at a speed of 20 rpm for 30 min, then take it out, wash it 3 times with deionized water and then dry it at 25°C for 3h to obtain the finished kapok fiber; the remaining steps are the same as in Example 2.

[0037] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: take 60 parts of deionized water, add 9 parts of methanol, heat to 50°C, add 12 parts of phenyltrimethoxysilane and 4 parts of methyltrimethoxysilane under stirring at 60rpm, react for 30min, add 0.6 parts of 2mol / L NaOH aqueous solution, react for 2h under stirring at 60rpm, filter the filtrate, wash it with deionized water 3 times, and dry it in an oven at 100°C for 2h to obtain copolymerized silsesquioxane microspheres with an average particle size of 30μm; prepare a bath solution with a concentration of 20g / L sodium hydroxide, 2g / L anhydrous sodium sulfate, and the rest of deionized water, weigh 5 parts of kapok fiber , put it into the bath liquid at a bath ratio of 1:40 and 100°C and boil it for 120 minutes, take out the kapok fiber, wash it with deionized water for 3 times, dry it at 25°C for 2 hours, put it into a flat electrode excitation processor for plasma treatment, the power is 2.5kW and the treatment time is 30 seconds, so as to obtain the pretreated kapok fiber; add 1.4 parts of copolymerized silsesquioxane microspheres and 0.8 parts of hollow magnesium hydroxide microspheres to 40 parts of tetrahydrofuran and stir at 60rpm for 20 minutes to obtain a mixed solution, soak 5 parts of the pretreated kapok fiber in the mixed solution, slowly stir it at 20rpm for 30 minutes, then take it out, wash it with deionized water for 3 times and then dry it at 25°C for 3 hours to obtain the finished kapok fiber; the remaining steps are the same as those in Example 2.

[0038] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different, and step (3) is changed to: three strands of finished kapok fiber are twisted into one strand and woven into an inner layer fabric; the outer layer is woven with cashmere fiber as the raw material and covered on both sides of the inner layer, the outer layer is composed of a first warp yarn, a first weft yarn, a second warp yarn and a second weft yarn, the first warp yarn, the first weft yarn, the second warp yarn and the second weft yarn are woven in an interlaced manner, and the first warp yarn and the first weft yarn are perpendicular to each other, and the second warp yarn and the second weft yarn are perpendicular to each other; the outer layer is woven and interlaced into the inner layer to form a gram weight of 450g / m 2 Sound insulation and flame retardant fabric; the remaining steps are the same as those in Example 2.

[0039] Effect example

[0040] Table 1 below shows the performance analysis results of a sound insulation and flame retardant fabric using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0041] Table 1

[0042]

[0043] From the comparison of the flame retardancy experimental data of the embodiment and the comparative example, it can be found that the present invention uses kapok fibers loaded with microspheres to weave into an inner layer, and cashmere fibers to weave into an outer layer to cover the front and back sides of the inner layer, which plays an effect of protecting and improving the touch of the fabric. Acrylic resin is used as a finishing cross-linking agent to treat the entire fabric. The acrylic resin finishing will form a thin film on the surface of the fabric fiber, and the two fibers are coated to cause cross-linking between the inner and outer fibers. The cashmere fiber also has a hollow structure. After the thermoplastic acrylic resin is used to coat the cashmere fiber, the molecular chain curls up when it is cooled and solidified. After film formation, the acrylic resin has high thermal expansion, and the resin volume inside the cashmere fiber is reduced. While improving the spinnability of the cashmere fiber, the hollow structure of the fiber is still retained, so that the fiber forms more and larger cavity structure residual carbon when burning, which synergizes with the hollow magnesium hydroxide particles attached to the inner kapok fiber to achieve a double-effect flame retardant effect. From the comparison of the experimental data of the sound insulation of the embodiment and the comparative example, it can be found that the present invention uses plasma treatment to produce numerous circular grooves on the surface of the kapok fiber due to the collision of the ion beam, which provides suitable attachment points for the positively charged hollow magnesium hydroxide microspheres and the polysiloxane microspheres with active hydroxyl groups. Since the polysiloxane microspheres can chemically bond with the kapok fibers and are fixed in the grooves, and the polysiloxane microspheres and the kapok fibers have negatively charged hydroxyl groups, the hollow magnesium hydroxide microspheres can be firmly adsorbed in the grooves on the surface of the kapok fibers through electrostatic bonding. At the same time, a large number of gaps are left between the polysiloxane microspheres and the magnesium hydroxide microspheres, which can synergize with the hollow structure of magnesium hydroxide and kapok fibers to achieve a strong sound insulation effect.

[0044] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A sound insulation and flame retardant fabric, characterized in that: The sound insulation and flame retardant fabric is a composite material formed by kapok fibers loaded with microspheres being woven into an inner layer and cashmere fibers being woven into an outer layer covering the front and back sides of the inner layer; The sound insulation and flame retardant fabric is prepared by the following method: (1) preparing a 0.1-2 mol / L magnesium sulfate aqueous solution, a 0.2-4 mol / L sodium hydroxide aqueous solution, and a 0.05 mol / L polyethylene glycol ether aqueous solution, mixing the magnesium sulfate aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 1:0.01-0.05 to form a mixed solution 1, and mixing the sodium hydroxide aqueous solution and the polyethylene glycol ether aqueous solution in a molar ratio of 2:0.01-0.05 to form a mixed solution 2, respectively passing through a pneumatic atomizing nozzle under the drive of compressed air to form an atomizing flow 1 and an atomizing flow 2, controlling the flow ratio of the liquid phase medium to the compressed air to be 1:7, collecting the magnesium hydroxide primary product after the spray impact precipitation is completed, and then stirring and aging for 1-3 hours, and then filtering the sample to obtain a filter cake, and drying it at 40° C. for 3 hours to obtain hollow magnesium hydroxide microspheres; (2) Take 60 parts of deionized water, add 6-12 parts of methanol, heat to 50°C, add 9-15 parts of phenyltrimethoxysilane and 1-7 parts of methyltrimethoxysilane under stirring at 60 rpm, react for 30 minutes, add 0.6 parts of NaOH aqueous solution, react for 2 hours under stirring at 60 rpm, filter the filtrate, wash it with deionized water for 3 times, and dry it in an oven at 100°C for 2 hours to obtain copolymerized silsesquioxane microspheres; weigh 5 parts of kapok fiber, put it into the bath at 100°C and boil it for 120 minutes, and then put the kapok fiber into the bath. The fiber was taken out, washed with deionized water for 3 times, dried at 25°C for 2 hours, and then placed in a flat electrode excitation processor for plasma treatment to obtain pretreated kapok fiber; 1.2-1.6 parts of copolymerized silsesquioxane microspheres and 0.6-1 parts of hollow magnesium hydroxide microspheres were added to 40 parts of organic solvent and stirred at 60 rpm for 20 minutes to obtain a mixed solution, 5 parts of pretreated kapok fiber were immersed in the mixed solution, slowly stirred at 20 rpm for 30 minutes, and then taken out, washed with deionized water for 3 times, and then dried at 25°C for 3 hours to obtain finished kapok fiber; (3) Three strands of finished kapok fiber are twisted into one strand and woven into an inner layer fabric; an outer layer is woven with cashmere fiber as raw material and covered on both sides of the inner layer, the outer layer is composed of a first warp yarn, a first weft yarn, a second warp yarn and a second weft yarn, the first warp yarn, the first weft yarn, the second warp yarn and the second weft yarn are woven alternately, and the first warp yarn and the first weft yarn are perpendicular to each other, and the second warp yarn and the second weft yarn are perpendicular to each other; the outer layer weaving is interlaced into the inner layer weaving to form a gram weight of 450g / m 2 Composite fabric: Put the composite fabric into the prepared acrylic resin finishing solution, the bath ratio is 1:10, the temperature is 120℃, soak for 45-75min, take it out, put it into an electric constant temperature blast drying oven at 60℃ and dry it for 1h to obtain the sound insulation and flame retardant fabric.

2. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The stirring speed during aging in step (1) is 600-1000 rpm.

3. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The concentration of the NaOH aqueous solution in step (2) is 2 mol / L.

4. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The average particle size of the polysiloxane microspheres in step (2) is 10-50 μm.

5. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The concentration of the bath solution in step (2) is 20 g / L sodium hydroxide, 2 g / L anhydrous sodium sulfate, and the rest is deionized water.

6. The sound insulation and flame retardant fabric according to claim 1, characterized in that: In the step (2), the bath ratio of the kapok fibers when they are boiled in the bath liquid is 1:

40.

7. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The plasma power in step (2) is 1.0-4.0 kW.

8. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The plasma treatment time in step (2) is 15-45s.

9. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The organic solvent in step (2) is tetrahydrofuran.

10. The sound insulation and flame retardant fabric according to claim 1, characterized in that: The finishing liquid in step (3) is an aqueous solution of acrylic resin with a concentration of 5-25 g / L.